Quantum regression in dephasing phenomena - Lonigro, Davide; Chruściński, Dariusz (Journal of Physics A: Mathematical and Theoretical, 2022)
We investigate the validity of quantum regression for a family of quantum Hamiltonians on a multipartite system leading to phase-damping reduced dynamics. After finding necessary and sufficient conditions for the CP-divisibility of the corresponding channel, we evaluate a hierarchy of equations equivalent to the validity of quantum regression under arbitrary interventions; in particular, we find necessary conditions for a nontrivial dephasing to be compatible with quantum regression. In this framework, we study a class of dephasing-type generalized spin-boson models, investigating the existence of qubit-environment coupling functions that ensure the exact validity of quantum regression.
Created from Fastlane, Scopus look-up
Keywords: CP-divisibility; dephasing channels; generalized spin-boson models; Markovianity of open quantum systems; quantum regression